THE STYLE OF THE CONFLICT RESOLUTION OF THE BOARDING SCHOOL IN BALI - haya (International Jurnal of Education Schoolars, 2022)
This research discusses Islamic boarding schools in Bali with the focus of study on conflict resolution styles from an Islamic perspective, namely their main duties and functions as a blessing for all mankind. Islam is a religion of peace that provides protection and a sense of security for people to do things according to their respective beliefs. This view underlies the existence of Article 29 of the 1945 Constitution which requires mutual respect and appreciation between fellow human beings regardless of SARA background. Conflict resolution practices in Bali in the form of tolerant pesantren show an inclusive attitude towards the surrounding community, and vice versa, namely the openness of the Balinese people towards Islamic development. Islamic boarding schools in Bali are open and willing to accept differences as a necessity that cannot be contained. They view differences and diversity in religion as a human and Indonesian nature, so they must be accepted as historical facts. At the Istiqlal Islamic Boarding School in Buleleng and Bali Bina Insani Tabanan there are sixteen teachers who are Hindu and Buddhist. This phenomenon is interesting to study in depth considering the sharp horizontal conflict experience between Muslims and non-Muslims in Bali. This means that Islamic boarding schools have a unique experience in terms of resolving horizontal conflicts between Muslims and non-Muslims.schools in Bali are increasing both qualitatively and in number boarding